Internal Jugular Phlebectasia; A Challenging Neck Mass in Children - Alsaeed, Gihad; Alsaeed, Ali; Hasan Aljindi, Mohamad; Alsaeed, Mohamed (Journal of Pediatric Health And Nutrition, 2024)
Cystic neck masses are uncommon in children, and a minority of them are soft. Internal jugular vein phlebectasia (IJVP) is a rare cause of soft neck cysts. It presents usually as a unilateral soft neck mass of changing size. In most cases it is unilateral, right sided and predominantly in males. Imaging study modalities are diagnostic and helpful for observation and follow up. In the vast majority of cases, it decreases in size with time requiring only conservative treatment. However, surgery might be necessary in large or complicated phlebectasia. IJVP is underdiagnosed or misdiagnosed especially in pediatrics, with few cases documented in medical literature. To improve awareness of presentation and management-plan of this rare case, the authors present an extremely rare case of huge left internal jugular phlebectasia in a 14 year-old boy worsened and complicated over years of wait and see approach that needed surgical treatment.
Keywords: Jugular phlebectasia; neck mass; complications; intervention.